STUDENTS’ LEARNING STYLE ANALYSIS IN ENHANCING DIFFERENTIATED INSTRUCTION AT SD NEGERI 1 ROWOHARJO - Dewi Sekar Sari; Dhea Ayu Laura; Anisa Nasywa Zhahiroh; Abu Rijal Maulana Bekti; Ferril Irham Muzaki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the variations in students' learning styles and their relationship with the implementation of differentiated instruction at SD Negeri 1 Rowoharjo. A systematic literature review (SLR) following the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was conducted on 11 selected articles retrieved from Google Scholar, SINTA, and nationally accredited journal portals, and was integrated with empirical field data obtained through in-depth interviews with three teachers. The findings consistently reveal that elementary school students possess heterogeneous learning styles, with a dominance of the kinesthetic modality followed by visual and auditory preferences. Teachers at SD Negeri 1 Rowoharjo have made efforts to accommodate these differences through the use of visual media, class discussions, and hands-on activities; however, such efforts remain situational and have not been grounded in systematic learning style mapping. Identification of learning styles through the VARK model proves to be a practical and relevant framework for designing adaptive instructional strategies. This study concludes that structured mapping of students' learning styles is an essential prerequisite for effective, innovative, and student-centered differentiated instruction.